Observational survey of financial difficulties among patients with multiple myeloma and chronic lymphocytic leukaemia treated at US community oncology clinics (Alliance A231602CD) - Antonia Bennett; Bruce David Rapkin; George J Chang; Gabriela Gracia; Selina Chow; Heather B Neuman; Stacie Dusetzina; Rena M Conti; Shaylene McCue; Travis Dockter; Heather Gunn; Shelley A Jazowski; et al. (BMJ Open)
Objectives To estimate the proportion and correlates of self-reported financial difficulty among patients with multiple myeloma (MM) or chronic lymphocytic leukaemia (CLL).Setting Sixty-six US community and minority oncology practices affiliated with the National Cancer Institute Community Oncology Research Programme (NCORP).Participants A total of 521 patients (≥18 years) with MM or CLL consented and 416 responded to a survey (completion rate=79.8%). Respondents had a MM diagnosis (74.0%), an associate degree or higher (53.4%), were White (89.2%), insured (100%) and treated with clinician-administered drugs (68.0%).Study design Observational, theoretical model and protocol-based patient survey administered between May 2019 and June 2020.Primary and secondary outcome measures Financial difficulty was assessed using a single-item measure, the EORTC QLQC30: ‘Has your physical condition or medical treatment caused you financial difficulties in the past year?’ and using an ‘any-or-none’ composite measure of 22 items assessing financial difficulty, worries and the use of cost-coping strategies. Multivariable logistic regression models assessed the association of financial difficulty with diagnosis, socioeconomic and treatment characteristics.Results About 16.8% reported experiencing financial difficulty using the single-item measure and 60.3% using the composite measure. Most frequently endorsed items in the composite measure were financial worry about having to pay large medical bills related to cancer and difficulty paying medical bills. Financial difficulty using the single-item measure was associated with having MM vs CLL (adjusted OR (aOR), 0.34; 95% CI, 0.13 to 0.84; p=0.02), having insurance other than Medicare (aOR, 2.53; 95% CI, 1.37 to 4.66; p=0.003), being non-White (aOR, 2.21; 95% CI, 1.04 to 4.72; p=0.04) and having a high school education or below (aOR, 0.36; 95% CI, 0.21 to 0.64; p=0.001). Financial difficulty using the composite measure was associated with having a high school education or below (aOR, 0.62; 95% CI, 0.41 to 0.94; p=0.03).Conclusions US patients with MM and CLL report financial difficulty, especially those with low socio-economic status. Interventions are needed to mitigate patients’ financial difficulty.Trial registration number NCT03870633.